2013
DOI: 10.1515/ijsl-2013-0060
|View full text |Cite
|
Sign up to set email alerts
|

Afrikaans in contact with English: endangered language or case of exceptional bilingualism?

Abstract: At present, discussions about potential language shift from African languages or Afrikaans to English are widespread in South Africa. This article focuses on the position of Afrikaans. Researchers interested in the position of Afrikaans today hold different views and there are some methodological prob lems with current studies. The main aim of this article is to problematize claims of language shift among Afrikaans speakers by analyzing relevant data from a larger scale survey of the language repertoires of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The open question at the end of the survey is analysed with Atlas.ti version 8. The analysis of the language repertoire survey data for participants of African home languages (Coetzee‐Van Rooy, 2012; 2014; 2016) and Afrikaans (Coetzee‐Van Rooy, 2013) as a home language were published elsewhere. The focus of this article is on the analysis of the language repertoires of the English home language participants that formed part of the longitudinal language repertoire study and that were not reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…The open question at the end of the survey is analysed with Atlas.ti version 8. The analysis of the language repertoire survey data for participants of African home languages (Coetzee‐Van Rooy, 2012; 2014; 2016) and Afrikaans (Coetzee‐Van Rooy, 2013) as a home language were published elsewhere. The focus of this article is on the analysis of the language repertoires of the English home language participants that formed part of the longitudinal language repertoire study and that were not reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a fairly standard variety of Afrikaans is spoken in Gauteng. Afrikaans was chosen as the other primary home language because although many Afrikaans children attend English schools, the acquisition of Afrikaans is generally well supported in language-rich home environments and exposure to Afrikaans teaching in the school context, potentially resulting in more balanced bilingualism (Coetzee-Van Rooy 2013).…”
Section: Isizulu and Afrikaansmentioning
confidence: 99%
“…English is increasingly being viewed in very favorable terms, attitudinally. However, as Coetzee‐Van Rooy (2012, 2013) has shown, this does not mean that monolingualism is a possibility in the foreseeable future, nor that attitudes towards the other languages are increasingly negative. English is one language that functions with others in sets, and other languages may be more important to the identity constructions of many (‘non‐native’ English‐speaking) South Africans than English itself.…”
Section: The Sociolinguistic Dynamics Of South African Englishesmentioning
confidence: 99%